2012
DOI: 10.1016/j.meatsci.2011.09.014
|View full text |Cite
|
Sign up to set email alerts
|

The effect of maternal linseed supplementation and/or lamb linseed supplementation on muscle and subcutaneous adipose tissue fatty acid composition of indoor lambs

Abstract: Eighty eight lambs were used in a 2×2 factorial arrangement 1) to investigate the effect of maternal dietary linseed supplementation and/or lamb linseed supplemented concentrate on growth performance, carcass fat quality and fatty acid (FA) composition of muscle and dorsal adipose tissue of indoor lambs 2) to study the relationships between subcutaneous fat quality and FA composition. Feeding linseed to ewes increased C18:3 n-3 (ALA) proportion in milk and therefore the ALA supply to suckling lambs. However, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 51 publications
2
18
2
Order By: Relevance
“…Birth weight of lambs was used as covariate during growth analysis. Weaning weights of suckling lambs and their ADG before weaning were not affected by different oil sources supplemented in their diets (Manso et al 2011, Berthelot et al 2012. Milk conversion ratio (kg milk/kg growth of suckling lambs) was almost not variable with the only difference (P<0.05) was observed for the 5 % SFO group, and for the 5 % SBO group when taking about male lambs ratio.…”
Section: Growth Rate Of Lambs and Blood Metabolitesmentioning
confidence: 90%
See 1 more Smart Citation
“…Birth weight of lambs was used as covariate during growth analysis. Weaning weights of suckling lambs and their ADG before weaning were not affected by different oil sources supplemented in their diets (Manso et al 2011, Berthelot et al 2012. Milk conversion ratio (kg milk/kg growth of suckling lambs) was almost not variable with the only difference (P<0.05) was observed for the 5 % SFO group, and for the 5 % SBO group when taking about male lambs ratio.…”
Section: Growth Rate Of Lambs and Blood Metabolitesmentioning
confidence: 90%
“…However, such results of the serum FA profile would mostly reflect those of the milk FAs of dams (Lurueña-Martinez et al 2010). According to Berthelot et al (2012), FA composition of muscle and adipose tissues in suckling lambs or kids depends on the milk FA profile which is strongly related to the composition of the diet of their dams with a greater change occurring after weaning. Sanz Sampelayo et al (2006) found that when supplementing the diets of dam goats with a fat source, the FA composition in the tissue fat of suckling kids was almost alike to that of their dams' milk FA composition.…”
Section: Blood Fatty Acid Profilementioning
confidence: 99%
“…Some authors found an increase of LC-PUFAn-3 in lambs fed linseed diets (Noci et al, 2011;Berthelot et al, 2012), while others did not observe any effect (Bas et al, 2007). Others found that feeding ewes a n-3-enriched diet in lactation increased the proportion of 18:3n-3 and their longer chain derivatives in suckling lamb muscles (Gómez-Cortés et al, 2014;Mele et al, 2014), whereas Berthelot et al (2012) did not report such effects in their earlier experiment. Some studies in human and laboratory animals suggest that the conversion of ALA into LC-PUFA homologs increases during pregnancy probably due to the agonistic effects of the female sex hormones estrogen and progesterone (Kitson et al, 2010).…”
Section: Introductionmentioning
confidence: 94%
“…Some of these studies are made in rabbit meat [51][52]32] and lamb meat [53]. While Kouba et al [32], reported that the enriched Longissimus dorsi did not exhibit a lower oxidative stability, Castellini et al [51] and Dal Bosco et al [52] found that feeding a n-3 PUFA enriched diet lowered significantly TBARS level in, raw meat and Longissimus dorsi.…”
Section: Quality Of Pufa Enriched Animal Products and Relation With Lmentioning
confidence: 99%